Nonlocal effects on Rayleigh-type surface wave in a micropolar piezoelectric medium - Singh, Baljeet; Sangwan, Asha; Singh, Jagdish (Vietnam Journal of Mechanics, 2022)
The properties of Rayleigh-type surface wave in a linear, homogeneous and transversely isotropic nonlocal micropolar piezoelectric solid half-space are explored. Dispersion relations for Rayleigh-type surface wave are derived for both charge free and electrically shorted cases. Using an algorithm of iteration method in MATLAB software, the wave speed of Rayleigh wave is computed for relevant material constants. The effects of nonlocality, angular frequency, micropolarity and piezoelectricity are illustrated graphically on the propagation speed of Rayleigh wave.